2021
DOI: 10.3390/s21093148
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Algorithm for In-City Parking Allocation: A Case Study of Al Madinah City

Abstract: Parking in heavily populated areas has been considered one of the main challenges in the transportation systems for the past two decades given the limited parking resources, especially in city centres. Drivers often waste long periods of time hunting for an empty parking spot, which causes congestion and consumes energy during the process. Thus, finding an optimal parking spot depends on several factors such as street traffic congestion, trip distance/time, the availability of a parking spot, the waiting time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Xiao et al (2018) prove that the loss queue model performs well in estimating the system parameters and making occupancy predictions. Abdeen, Nemer, & Sheltami (2021) investigate the loss queue model to estimate the availability of parking spots in a parking lot. They derive this performance measure based on the arrival and service rates of vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xiao et al (2018) prove that the loss queue model performs well in estimating the system parameters and making occupancy predictions. Abdeen, Nemer, & Sheltami (2021) investigate the loss queue model to estimate the availability of parking spots in a parking lot. They derive this performance measure based on the arrival and service rates of vehicles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdeen et al invented a parking spot allocation algorithm for parking allocation. The proposed system considered real-time street traffic while choosing the optimal parking spot [275]. Al-Shariff et al suggested using an Intelligent Transportation System (ITS) that is based on both Autonomous Electric Vehicles (AEVs) and IoT [276].…”
Section: H Transportationmentioning
confidence: 99%
“…Due to massive urbanization, traffic volume in urban areas has grown, making urban life very congested and polluted, leading to many negative impacts on human life, such as higher energy consumption, global warming, and airborne diseases [1]. According to World Resource Institute [2], 74% of CO 2 is produced by greenhouse gas emissions, and 93% of it results from fossil fuel usage, transportation, manufacturing, and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The data from occupancy sensors allows us to learn availability patterns and predict probabilities of parking occupancy of the spots. Based on Parking Sensor Data (PSD), various machine learning methods have been used to predict parking occupancy rates [1,11]. The most common ML used for parking prediction are Regression Trees [12][13][14], DTs [14], Support Vector Machine [13,15], Genetic Algorithm [16], Bayesian [17], and Neural Network [13,18].…”
Section: Introductionmentioning
confidence: 99%